2006
DOI: 10.1007/s00428-006-0313-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential pathological understaging of pT3 rectal cancer with less than 26 lymph nodes recovered: a prospective study based on a resampling of 50 rectal specimens

Abstract: The aim of the paper was to establish if the 12 lymph nodes recommended by tumor-node-metastasis (TNM) system are sufficient for a correct staging of rectal cancer. For this purpose, we first compared the mean number of lymph nodes recovered in the same surgical specimen at the routine sampling and at a resampling performed by a second expert gastrointestinal pathologist. The study was performed on 50 cases of pT2N0 and pT3N0 rectal cancers, with a minimum number of 12 lymph nodes recovered at first sampling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
7
15
0
Order By: Relevance
“…In a large series of colorectal cancers reported by Goldstein [1], about 30% of pT3N+ patients had a single metastatic lymph node, and the percentage of specimens with one lymph-node metastasis increased from 41.62 to 80.36% when the number of lymph nodes increased from 11-15 to more than 21, respectively. Notably, in our study, we obtained similar results, as all restaged pT3N+ patients had only a single metastatic lymph node, which was found in specimens in which a minimum number of 19 lymph nodes had been originally detected [2]. Accordingly, we propose that at least 20 lymph nodes should be recovered as an acceptable mean number in a series of colorectal cancer dissections.…”
Section: Dear Sirsupporting
confidence: 88%
See 3 more Smart Citations
“…In a large series of colorectal cancers reported by Goldstein [1], about 30% of pT3N+ patients had a single metastatic lymph node, and the percentage of specimens with one lymph-node metastasis increased from 41.62 to 80.36% when the number of lymph nodes increased from 11-15 to more than 21, respectively. Notably, in our study, we obtained similar results, as all restaged pT3N+ patients had only a single metastatic lymph node, which was found in specimens in which a minimum number of 19 lymph nodes had been originally detected [2]. Accordingly, we propose that at least 20 lymph nodes should be recovered as an acceptable mean number in a series of colorectal cancer dissections.…”
Section: Dear Sirsupporting
confidence: 88%
“…There is no general consensus about this number if other authors, recently reporting colorectal cancer guidelines, propose a mean number of 15-18 lymph nodes [6]. Recently, we have published in Virchows Archiv a paper showing that in pT3 rectal cancer, 12-15 lymph nodes are insufficient for a correct staging [2]. In that prospective study, we first showed that if the mean number of lymph nodes recovered increased from 17.8 to 26.8, after a second sampling of the same surgically resected specimens, metastases were detected in 18.7% of patients that had been originally understaged [2].…”
Section: Dear Sirmentioning
confidence: 97%
See 2 more Smart Citations
“…Lymphadenectomy is the most important prognostic factor in pelvic malignancies, a finding that has substantially changed surgical approaches from a "quantitative" premise to a more "qualitative" nature giving priority to the psycho-physical integrity of cancer patients by limiting the surgical intervention (Breyer et al, 2008;Mills et al, 2006;Desnoo & Faithfull 2006;Greco et al, 2006). However, despite progress made by the conservative surgical approach for rectal cancer, the development of functional abnormalities in patients undergoing conservative surgery has become more evident (Ortiz & Armendariz, 1996).…”
Section: Introductionmentioning
confidence: 99%